PENERAPAN METODE BERMAIN PERAN UNTUK MENINGKATKAN KETERAMPILAN SOSIAL DAN KETERAMPILAN BERKOMUNIKASI SISWA TK - Bellina, Olivia (JDMP (Jurnal Dinamika Manajemen Pendidikan), 2019)
Research is based on existing problems in the classroom, in the form of inadequate students social skills communication skills. The purpose of this study was to analyse the process of applying role playing methods to improve social skills and communication skills, analyse the development of social skills and communication skills after the application of role-playing methods, and describe constraints during the process of applying role methods. The research with subject of 15 children took place at Kindergarten A School X West Jakarta. The researcher carried put the research using the class action research (CAR) method through the application of role-playing method in three cycles. Data is collected through observation, field notes and documentation. The results of this study shows that the method of role-playing method of role-playing with the theme of hospital, restaurant, and traditional market can improve social skills and communication skills. The target of 80% that was set after the application of role-playing method was reached in the third cycle.